MEKANISME PEMBERIAN KREDIT MODAL KERJA PADA PD. BPR. BAHTERAMAS KENDARI - imran, laode; kambolong, makmur; sahrun, sahrun (Business UHO: Jurnal Administrasi Bisnis, 2017)
Banks have a very important role in terms of processing funds or allocating public funds to provide funds to the public in the form of credit. Credit control plays a very important role. Therefore, in granting credit must be with caution and with a credit control system that is good and right. This study aims to find out how to analyze the system and procedures for granting working capital loans applied by PD. BPR. Bahteramas Kendari. This type of research used by the author is descriptive research with a qualitative approach.From the results of the study, the authors know several weaknesses in the procedure for granting working capital loans and credit control as in the stage of credit analysis that there are still double tasks. In addition, in controlling credit there are also some deficiencies that may need to be corrected, such as the documents that are used inappropriately, and process improvements that are easier to understand from the time of credit application until the time of credit disbursement. Suggestions that can be given are the separation of tasks for the assessment of collateral or collateral and credit analysis assessment, there is a register of prospective customer forms at the time of the credit application contained in the identity of the prospective debtor to minimize fraud in the loan application.